Maternal stress during pregnancy and neurodevelopmental outcomes of children during the first 2 years of life. (6th February 2017) - Polanska, Kinga; Krol, Anna; Merecz‐Kot, Dorota; Jurewicz, Joanna; Makowiec‐Dabrowska, Teresa; Chiarotti, Flavia; Calamandrei, Gemma; Hanke, Wojciech
Abstract : Aim: A growing body of literature documents associations between maternal stress in pregnancy and child development, but findings across studies are often inconsistent. The aim of this study was to estimate the association between exposure to different kinds of prenatal stress and child psychomotor development. Methods: The study population consisted of 372 mother‐child pairs from Polish Mother and Child Cohort. The analysis was restricted to the women who worked at least 1 month during pregnancy period. Maternal psychological stress during pregnancy was assessed based on: the Subjective Work Characteristics Questionnaire, Perceived Stress Scale and Social Readjustment Rating Scale. The level of satisfaction with family functioning and support was evaluated by APGAR Family Scale. Child psychomotor development was assessed at the 12th and 24th months of age by Bayley Scales of Infant and Toddler Development. Results: Negative impact on child cognitive development at the age of two was observed for the Perceived Stress Scale (β = −0.8; P = 0.01) and the Social Readjustment Rating Scale (β = −0.4; P = 0.03) after adjusting for the variety of confounders. Occupational stress, as well as satisfaction with family functioning, was not significantly associated with child psychomotor development ( P > 0.05). Conclusions: The study supports the findings that prenatal exposure to maternal stress is significantly associated with decreased child cognitive functions. In order to further understand and quantify the effects of prenatal stress on child neurodevelopment further studies are needed. This will be important for developing interventions that provide more assistance to pregnant women, including emotional support or help to manage psychological stress.